Kaizen and Healthcare: A Bibliometric Analysis (Revista do LabDGE - UFF, 2023)
The objective of this article was to map the state of the art, by means of bibliometric research, of how the scientific evolution of Kaizen has been occurring in theory, in practice and, especially, in the health area around the world, in order to guide future research in the same, as, for example, kaizen has been contributing to humanization within health centers. A broad structured search was performed using keywords and Boolean logic, in the PubMed, ISI and Scopus data bases. The identified publications were cataloged in EndNote and NVIVO 10 software for bibliometric analysis. Through these, 1,467 publications were identified, in the three databases, excluding the repeated publications and those without relevant information. The main key terms identified and in common in all publications were: “management”, “lean”, “quality” and “kaizen”; and the authors who publish the most were Van Aken, E.M., Farris, J. A., Suárez-Barraza, M.F. and Glover, W. J; and when kaizen applied to healthcare was evaluated, the most cited article among the 1,467 selected was the “Lean in healthcare: The unfilled promise?”, by Radnor, ZJ, Holweg, M. and Waring, J., which has 316 citations in Scopus. It was evidenced that kaizen applied to health still has much potential to expand.